2003
DOI: 10.1038/sj.bjc.6600782
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, body weight, and pancreatic cancer mortality

Abstract: In a study of 32 687 subjects with data on physical activity and body mass index (BMI) collected serially over time, we examined associations with pancreatic cancer mortality (n ¼ 212). Despite plausible biologic mechanisms, neither physical activity (multivariate relative risks for increasing levels: 1.00, 0.98, 0.92, and 1.31, respectively) nor BMI (corresponding findings: 1.00, 0.84, 1.08, and 0.99, respectively) significantly predicted pancreatic cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 26 publications
1
32
1
Order By: Relevance
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 93%
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women. Similar to cohort studies, case-control studies have also produced contradictory results with a meta-analysis carried out in 2003 concluding that the risk of pancreatic cancer was only weakly associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall six case -control (Bueno de Mesquita et al, 1990;Howe et al, 1990;Ghadirian et al, 1991;Zatonski et al, 1991;Silverman et al, 1998;Hanley et al, 2001) and eight cohort studies (Friedman and van den Eeden, 1993;Shibata et al, 1994;Gapstur et al, 2000;Michaud et al, 2001;Stolzenberg-Solomon et al, 2002;Calle et al, 2003;Lee et al, 2003) were eligible for inclusion in this metaanalysis. In total, these studies included 6391 cases of pancreatic cancer ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, study done by Ghorbani Z et al [29] have shown in a well-matched case control study that increased frequency of intake of rice, bread and barbequed meat and deep fried vegetables can aggregate the risk while consumption of fish can decrease the incidence of pancreatic cancer. There has been no association between intake of fat and risk of pancreatic cancer [30] while exercise, which helps to maintain normal body weight, has been associated with a reduced risk of pancreatic cancer [31]. Non-steroidal anti-inflammatory drugs (NSAIDs), mainly aspirin, have shown to decrease risk of pancreatic cancer [32,33]; however, other non-aspirin NSAIDs have not shown the benefit [34].…”
Section: Dietmentioning
confidence: 99%